ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦å¸ˆèŒƒæ•™è‚²å¦é™¢æ±‰è¯ä¸“ä¸š2015å±ŠAçå¦ç”Ÿ ä½¿ç”¨æ±‰è¯åŠ©åŠ¨è¯â€œèƒ½â€å’Œâ€œä¼šâ€çš„åè¯¯åˆ†æž - Wati, Winda Widia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractAuxiliary verb is the most important part of verb. It is used to help the main verb in explaining sentences about ability, possibility, or anxiety. For example, ?neng? and ?hui? auxiliary verb they both are difficult to be mastered because they have similar meaning and also complicated way of using. That make students tend to make errors in using these auxiliary verb.To know the common errors and the cause of students' errors in studying ?neng?and ?hui?, the writer did the research on the use of ?neng?and ?hui?  to A class students of Mandarin Language Education on Teacher Training and Education Faculty of Tanjungpura University in Academic Year 2015. After the research done, it could be concluded that the percentage of students' error in using ?neng?and ?hui?  on A class students of Mandarin Language Education on Teacher Training and Education Faculty of Tanjungpura University in Academic Year 2015 are 46,35% and 40,63%. Thee common errors are word selection and word order. The influence of mother tongue and foreign language that have been learned by the students are the causes of students' errors. Based on above problems, the writer give some suggestions for teachers in teaching process. Keywords: Auxiliary Verb ?neng? and ?hui?, Error Analysis